Preparation of a wood pitch-based porous carbon material and its application in 3D printed supercapacitors

By combining wood asphalt with rosin derivatives, a porous carbon material with controllable structure was prepared and combined with PEDOT:PSS, the problem of insufficient energy density and rate performance of electrode materials in the prior art was solved, and high specific capacitance and Electrode material with good cycle stability.

CN118545713BActive Publication Date: 2025-02-11FUJIAN AGRI & FORESTRY UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410676807.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-29
Publication Date
2025-02-11
Estimated Expiration
2044-05-29

AI Technical Summary

Technical Problem

The existing 3D printed supercapacitor electrode materials based on PEDOT:PSS have problems with low printing electrode thickness and energy density. At the same time, the preparation process of printable inks is complex and toxic solvents are often used.

Method used

Wood asphalt is used as the precursor, oxygen-containing functional groups are introduced through chemical oxidation, and combined with rosin derivatives to regulate the size of carbon nanosheets to form a porous carbon material with controllable structure. This material is combined with PEDOT:PSS to prepare an electrode material with high energy density and high magnification properties.

Benefits of technology

Achieve high specific surface area and excellent electrochemical performance. The specific capacitance reaches 376 F/g at a current density of 1 A/g, and after cycling for 5000 cycles at a current density of 10 A/g, the specific capacitance retention rate reaches 83.8%. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118545713B_ABST
    Figure CN118545713B_ABST
Patent Text Reader

Abstract

The invention discloses a wood asphalt-based porous carbon material and a preparation method thereof, wherein wood asphalt is reacted with hydrogen peroxide to obtain oxidized wood asphalt, the oxidized wood asphalt is mixed with chitosan and acrylic rosin for pre-carbonization, and the obtained product is mixed with KOH for activation, thereby obtaining a rosin-wood asphalt-based porous carbon material. Using direct ink writing technology (DIW), the composite ink obtained by using the rosin-wood asphalt-based porous carbon material obtained by the invention as a raw material can be printed into an electrode, thereby being used for the preparation of a fully gel-state micro supercapacitor, and the obtained supercapacitor has both excellent printing performance and electrochemical activity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of material preparation, and in particular relates to a method for preparing a wood asphalt-based porous carbon material and an application of the material in ink for 3D printing supercapacitors. Background Art

[0002] Micro-supercapacitors have become a research hotspot in the field of energy storage due to their high power density, long cycle life, and fast charging and discharging capabilities. However, further improving their energy density and rate performance remains a major challenge. To this end, researchers have done a lot of work in developing new electrode materials with high specific surface area and high conductivity, such as developing advanced carbon materials, and optimizing electrode structure design to achieve rapid transmission of electrons and ions. In recent years, advanced manufacturing technologies such as laser etching, photolithography, inkjet printing, screen printing, and 3D printing have been widely used in the preparation of supercapacitor electrodes. Among them, direct-ink writing (DIW) 3D printing technology has become a hot method for preparing micron-level fine and complex electrode structures due to its advantages of low cost, high efficiency, and customizable patterns, and is expected to meet the needs of customization and large-scale production.

[0003] When 3D printing supercapacitor electrodes, it is crucial to prepare viscoelastic inks with appropriate rheological properties. Currently, a variety of electrochemically active materials such as graphene, conductive polymers, and transition metal carbides have been used to develop printable inks. Poly(3,4-ethylenedioxythiophene):Polystyrene Sulfonate (PEDOT:PSS), as a conductive polymer, has tunable electrical properties, excellent redox activity, good structural stability, and biocompatibility, and is one of the most promising electrode materials. Compared with other conductive polymers (such as polyaniline and polypyridine), PEDOT:PSS has superior water solubility, easy processing, and tunable mechanical properties, making it an ideal electrode material for 3D printed micro-supercapacitors. However, current 3D printing research based on PEDOT:PSS electrodes still has shortcomings such as low printed electrode thickness and energy density. In addition, the preparation process of printable inks is relatively complex, and toxic solvents are often used. There is an urgent need to develop environmentally friendly PEDOT-based DIW inks.

[0004] Wood pitch is a solid formed by cooling and solidifying the black viscous oily substance remaining in the kettle during the distillation of wood tar. It is a renewable biomass resource with a wide range of sources, low price and unique structure. Although the application of coal tar pitch materials in the preparation of carbon materials has been widely studied, there are relatively few studies on wood pitch as a carbon material. In contrast, wood pitch has a lower coking value and less polycyclic aromatic hydrocarbon emissions, showing its potential as a precursor of carbon materials. Therefore, if a conductive polymer is composited with a wood pitch-based porous carbon material, it is expected to exert a synergistic effect and obtain an electrode material with both high energy density and high rate performance.

[0005] Rosin is a special forest resource in my country. Its main component is resin acid, which contains functional groups such as carboxyl and conjugated double bonds. Its unique chemical structure makes it particularly valuable in the research and development of sustainable materials. If rosin and its derivatives are introduced into the design of wood pitch-based carbon materials, the specific molecular size and chemical reactivity of the carboxyl and conjugated double bonds in the rosin molecules can be used to control the interlayer size of carbon nanosheets, and it is expected to obtain carbon nanosheet materials with controllable structure and excellent performance, providing new ideas and methods for the development of high-performance electrode materials. Summary of the invention

[0006] The object of the present invention is to provide a method for preparing a wood pitch-based porous carbon material and its application in preparing a 3D printed supercapacitor.

[0007] To achieve the above object, the present invention adopts the following technical solutions:

[0008] A wood pitch-based porous carbon material, the preparation method of which comprises the following steps:

[0009] 1) Preparation of oxidized wood asphalt: After the wood asphalt is pre-treated by ball milling, hydrogen peroxide is added for ultrasonic mixing, and then heated in a water bath for reaction, and then washed, filtered, and dried to obtain oxidized wood asphalt;

[0010] 2) Preparation of rosin-wood pitch-based porous carbon material: Grind and mix the oxidized wood pitch obtained in step 1) with chitosan and acrylic rosin, then pre-carbonize under nitrogen protection, and then grind and mix the obtained product with KOH, and activate it under nitrogen protection. The activated product is acid-washed, washed with water, and dried to obtain a rosin-wood pitch-based porous carbon material.

[0011] Furthermore, in step 1), the amount of hydrogen peroxide used is 0.5-3 mL per gram of wood asphalt.

[0012] Furthermore, the ball milling pretreatment time in step 1) is 1-9 h.

[0013] Furthermore, the reaction temperature in step 1) is 60-90°C and the reaction time is 1-3 h.

[0014] Furthermore, the mass ratio of oxidized wood asphalt, chitosan, acrylic rosin and KOH used in step 2) is 1:1:(0-0.25):3.

[0015] Furthermore, the pre-carbonization temperature in step 2) is 400-600°C and the time is 0.5-3 h.

[0016] Furthermore, the activation temperature in step 2) is 600-1000°C and the activation time is 0.5-3 h.

[0017] Furthermore, the pickling in step 2) is performed by soaking in 1 mol / L HCl solution for 7 h.

[0018] The obtained wood asphalt-based porous carbon material can be used for the preparation of 3D printed supercapacitors, which specifically includes the following steps:

[0019] a) Preparation of wood asphalt-based composite ink: adding the wood asphalt-based porous carbon material, glycerol system nanocellulose, and ethylene glycol into a PEDOT:PSS aqueous solution and stirring and mixing, and then heating and concentrating to obtain a wood asphalt-based composite ink;

[0020] b) Preparation of gel electrolyte: PVA powder was added to 1 mol / L H 2 SO 4 The solution was stirred vigorously at 85 °C until the solution became transparent to prepare PVA / H 2 SO 4 Gel electrolyte;

[0021] c) Preparation of encapsulation solution: adding styrene block copolymer into toluene and continuously stirring vigorously at 65°C until the solution becomes transparent to prepare encapsulation solution;

[0022] d) Preparation of supercapacitors: The wood asphalt-based composite ink prepared in step a) was printed uniformly layer by layer on a PTFE board using direct ink writing (DIW) technology. After printing, the obtained electrodes were cut and fixed on a glass slide with double-sided tape. Then, conductive silver paste was coated on both sides of the electrodes and dried in an oven at 60 °C for 10 min. Then, the PVA / H prepared in step b) was placed on the PTFE board. 2 SO 4 The gel electrolyte is poured on the electrode and dried under ventilation at room temperature. Then the encapsulation liquid prepared in step c) is directly coated on the entire device for encapsulation and dried under ventilation at room temperature to obtain a micro supercapacitor.

[0023] Furthermore, the glycerol system nanocellulose in step a) is prepared by placing 10 g of pulp into 50-100 g of glycerol, adding 0.2-1 g of a 72% sulfuric acid solution as a catalyst, heating in an oil bath at 80-120°C and vigorously stirring for 1-4 h to completely dissolve the pulp board; after the reactants are cooled to room temperature, adjusting the pH to neutral with a 5% NaOH solution, and then transferring to a colloid mill for mechanical treatment for 0.5-1 h to obtain the obtained product.

[0024] Furthermore, in step a), the total mass concentration of the PEDOT:PSS aqueous solution is 1%, wherein the mass ratio of PEDOT to PSS is 1:2.5.

[0025] Furthermore, in step a), the usage ratio of rosin-wood pitch-based porous carbon material, glycerol system nanocellulose, ethylene glycol and PEDOT:PSS aqueous solution is (0-0.2) g: 1 g: 4 mL: 16 mL.

[0026] Furthermore, the heating and concentration in step a) is carried out at a temperature of 60-100° C. and for a time of 2-4 hours.

[0027] Further, in step b), the PVA powder and H 2 SO 4 The dosage ratio of the solution is 1g / 10mL.

[0028] Furthermore, the mass ratio of the styrene block copolymer to toluene used in step c) is 9:51.

[0029] The present invention adopts H 2 O 2 Oxidative pretreatment of wood asphalt can selectively introduce oxygen-containing functional groups at the edges of polycyclic aromatic hydrocarbons in wood asphalt to improve its hydrophilicity and reaction activity. Subsequently, rosin groups are further introduced into the oxidized wood asphalt molecules, which can effectively adjust the distance between wood asphalt molecules and prevent excessive accumulation of molecules, which is beneficial to the subsequent KOH intercalation activation and promotes the formation of a porous structure.

[0030] The significant advantages of the present invention are:

[0031] (1) The present invention uses wood asphalt as a precursor, and utilizes its characteristics of being rich in aromatic structures and functional groups to selectively introduce oxygen-containing functional groups through chemical oxidation to improve the dispersibility of wood asphalt in polar solvents and provide reactive sites. At the same time, a rosin derivative with a specific structure is selected to react with the oxygen-containing functional groups on the surface of wood asphalt to introduce controllable nanogaps between carbon nanosheets to form a molecular-scale "pillared" structure. During the high-temperature heat treatment process, the rosin derivative can further adjust the surface chemical properties and structure of the carbon material through self-assembly induction and chemical activation strategies to obtain a porous carbon electrode material with controllable structure and excellent electrochemical performance.

[0032] (2) The wood pitch-based porous carbon material obtained by the present invention is combined with the conductive polymer PEDOT:PSS, and the rosin-wood pitch-based carbon material (RWPC) is used as the active substance, the PEDOT:PSS conductive polymer is used as the conductive network, and the glycerol system nanocellulose is used as the rheological agent to improve the ink's adhesion and the ability to accommodate the active substance. A conductive polymer / rosin-wood pitch-based carbon material (PEDOT:PSS / RWPC) composite electrode ink with excellent capacitance performance can be prepared. The composite electrode ink has good shear thinning behavior and stability. It is prepared into an electrode using direct ink writing (DIW) technology, and then PVA / H 2 SO 4 As an electrolyte, a fully gel-state micro-supercapacitor with excellent printing performance and electrochemical activity can be produced. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 This is a process flow chart for assembling supercapacitors using composite ink in the embodiments.

[0034] Figure 2 The nitrogen adsorption-desorption isotherms (a) and pore size distribution curves (b) of the rosin-wood pitch-based porous carbon materials prepared with different amounts of acrylic rosin added in the examples.

[0035] Figure 3 The electrochemical performance diagram of rosin-wood pitch-based porous carbon materials prepared with different amounts of acrylic rosin added in the examples, where (a) is the CV curve at a scan rate of 100 mV s-1, and (b) is the current density of 1 A·g -1 (c) is the GCD curve when , and (c) is the relationship between specific capacitance and current density.

[0036] Figure 4 This is a SEM image of the rosin-wood pitch based porous carbon material RWPC-0.2 prepared in the example.

[0037] Figure 5The electrochemical impedance spectra of rosin-wood pitch-based porous carbon materials prepared with different amounts of acrylic rosin added in the examples.

[0038] Figure 6 This is the cycling performance diagram of the RWPC-0.2 sample prepared in the example at a current density of 10 A / g (the inset is the last three charge and discharge curves).

[0039] Figure 7 The figure is a printing effect diagram using the composite ink prepared in the embodiment.

[0040] Figure 8 Steady-state viscosity scanning curves (a) and dynamic stress scanning curves (b) of different composite inks in the entire shear rate range.

[0041] Fig. 9 Thixotropy curves of different composite inks at different shear rates.

[0042] Fig.10 The macroscopic morphology image (a), FESEM image (b) and SEM images (c, d) taken by biological cryo-electron microscopy of the interdigital electrodes prepared by 3D printing in the embodiment.

[0043] Fig.11 CV curves of interdigital electrodes prepared with different composite inks in the examples.

[0044] Fig.12 GCD curves of interdigital electrodes prepared with different composite inks at different current densities in the examples.

[0045] Fig.13 The surface capacitance (a) and EIS spectra (b) of the interdigital electrodes prepared with different composite inks at different current densities in the examples. DETAILED DESCRIPTION

[0046] The preparation of a wood pitch-based porous carbon material comprises the following steps:

[0047] 1) Preparation of oxidized wood asphalt: After the wood asphalt is pretreated by ball milling for 1-9 h, 0.5-3 mL / g of hydrogen peroxide is added and ultrasonically mixed, and then heated in a water bath at 60-90 °C for 1-3 h, and then washed, filtered, and dried to obtain oxidized wood asphalt;

[0048] 2) Preparation of rosin-wood pitch-based porous carbon material: The oxidized wood pitch obtained in step 1) was ground and mixed with chitosan and acrylic rosin, and then pre-carbonized at 400-600 °C for 0.5-3 h under nitrogen protection, and then the obtained product was ground and mixed with KOH, and activated at 600-1000 °C for 0.5-3 h under nitrogen protection. The activated product was soaked in 1 mol / L HCl solution for 7 h, and then washed and dried to obtain rosin-wood pitch-based porous carbon material. The mass ratio of oxidized wood pitch, chitosan, acrylic rosin and KOH used was 1:1:(0-0.25):3.

[0049] In order to make the contents of the present invention easier to understand, the technical solution of the present invention is further described below in conjunction with specific implementation methods, but the present invention is not limited thereto.

[0050] The preparation method of glycerol system nanocellulose is as follows: 10 g of pulp is put into 100 g of glycerol, and 1 g of sulfuric acid solution with a volume concentration of 72% is added as a catalyst, and the mixture is heated in a 120°C oil bath and stirred vigorously for 3 h to completely dissolve the pulp board; after the reactants are cooled to room temperature, the pH is adjusted to neutral with a NaOH solution with a mass concentration of 5%, and then the mixture is transferred to a colloid mill for mechanical treatment for 0.5 h to obtain the glycerol system nanocellulose. Example

[0051] 1. Preparation of Oxidized Wood Pitch

[0052] 10 g of wood asphalt was pre-treated by ball milling at 500 r / min for 3 h and then placed in a 50 mL beaker. 20 mL of H 2 O 2 , then ultrasonically treated in an ultrasonic water bath for 30 min, then heated and stirred in an 80 ℃ water bath for 2 h, finally washed with deionized water, filtered to neutrality, and dried in an 80 ℃ oven to obtain oxidized wood asphalt.

[0053] 2. Preparation of rosin-wood pitch-based porous carbon materials

[0054] 1 g of oxidized wood pitch and 1 g of chitosan were weighed and mixed with 0, 0.05, 0.1, 0.15, 0.2 and 0.25 g of acrylic rosin in an agate mortar, respectively. Then, they were placed in a corundum boat, which was placed in a tube furnace and heated to 500 ℃ at a rate of 2 ℃ / min in a high-purity nitrogen atmosphere and kept at this temperature for 1 h for pre-carbonization. Then, the pre-carbonized product was taken out, quickly ground with 3 g of KOH, and then placed in a corundum boat. The temperature was raised to 800 ℃ at a rate of 5 ℃ / min in a nitrogen atmosphere and kept at this temperature for 1 h for chemical activation. The activated product was soaked in 1 mol / L HCl solution for 7 h, then filtered and rinsed with deionized water until neutral, and dried at 80 ℃ for 12 h to obtain rosin-wood pitch based porous carbon materials (RWPC). According to the amount of acrylic rosin added, the final products were named RWPC-0, RWPC-0.05, RWPC-0.1, RWPC-0.15, RWPC-0.2 and RWPC-0.25.

[0055] 3. Preparation of composite ink

[0056] 1 g of glycerol system nanocellulose (GCNCs), 4 mL of ethylene glycol and 0, 40, 120, 200 mg of rosin-wood pitch-based porous carbon material (RWPC-0.2) were added to 16 mL of PEDOT:PSS aqueous solution with a total mass concentration of 1%, stirred for 1 h to form a uniform dilute suspension, and then heated and concentrated at 80 ° C for 4 h to obtain direct-inkwriting composite ink (DIW), which was named DIW-0, DIW-40, DIW-120 and DIW-200 according to the different amounts of rosin-wood pitch-based porous carbon material. The prepared DIW composite ink was sealed and stored in a refrigerator at about 4 ° C before use.

[0057] 4. Preparation of Gel Electrolyte

[0058] Add 3g PVA powder to 30ml 1 mol / L H 2 SO 4 The solution was stirred vigorously at 85 °C until the solution became transparent to prepare PVA / H 2 SO 4 Gel electrolyte.

[0059] 5. Preparation of Encapsulation Solution

[0060] 4.5 g of styrene block copolymer particles were added to 25.5 g of toluene and stirred vigorously at 65 °C until the solution became transparent to prepare an encapsulation solution.

[0061] 6. DIW 3D printing process

[0062] like Figure 1 , the preparation of micro supercapacitors using a microelectronic printer mainly includes the following steps:

[0063] (1) Electrode printing: The prepared composite ink is loaded into a 10 mL syringe and assembled with a nozzle with an inner diameter of 410 μm. The device is then mounted on the printer's dispensing accessory and fixed to the printer stand. The electrode pattern and routing method are pre-designed on the computer, and the corresponding printing parameters are optimized, including the printing speed (5 mm / s) and the printing pressure (60 kPa). The PTFE sheet is placed on the printer substrate and the printing process is performed. The printer will print the ink evenly layer by layer on the PTFE sheet according to the preset design. After printing, the electrode is stored in a refrigerator at about 0 °C.

[0064] (2) Device assembly: The printed interdigitated electrodes were cut and fixed on a glass slide with double-sided tape. Then, conductive silver paste was applied on both sides of the electrodes and dried in an oven at 60 °C for 10 min. 2 SO 4 The gel electrolyte is poured on the interdigital electrodes and dried naturally in a fume hood at room temperature to make it lose most of its fluidity. Finally, the encapsulation liquid is directly coated on the entire device and dried naturally in a fume hood at room temperature to obtain an assembled symmetrical micro-supercapacitor.

[0065] result:

[0066] 1. Specific surface area and pore size analysis of rosin-wood pitch-based porous carbon materials

[0067] The pore structure of the obtained rosin-wood pitch-based porous carbon material was investigated by nitrogen adsorption-desorption isotherms. Figure 2 As shown. Figure 2 It can be seen that the rosin-wood pitch-based porous carbon materials prepared with different amounts of acrylic rosin addition all have type I isotherms. 0 <0.1, the nitrogen adsorption capacity increases rapidly, while P / P 0=0.4-0.8, and there is a hysteresis loop, indicating that there are abundant micropores-mesopores in the sample (a). This hierarchical porous structure is extremely beneficial for the transmission and migration of electrolyte ions in the electrode material. The pore size distribution diagram of the sample further confirms that the pore size of the obtained rosin-wood pitch-based porous carbon material is mainly concentrated in the micropores of 0.7 nm and the mesopores of 1-10 nm (b).

[0068] The pore structure parameters of the samples are shown in Table 1.

[0069] Table 1 Specific surface area and pore structure parameters of rosin-wood pitch-based porous carbon materials prepared with different amounts of acrylic rosin added

[0070]

[0071] As shown in Table 1, the addition of acrylic rosin can effectively increase the specific surface area of ​​the sample. When 0.2 g of acrylic rosin is added, the specific surface area increases from 3182.6 m 2 / g increased to 3521.5 m 2 / g, combined with KOH activation, can create abundant micropores to achieve a reasonable pore size distribution of carbon materials, thereby affecting the electrochemical properties of the materials. At the same time, the micropore porosities of RWPC-0.15, RWPC-0.2 and RWPC-0.25 are 0.29, 0.58 and 0.49, respectively, which indicates that excessive addition of acrylic rosin will cause some micropores to collapse and transform into mesopores.

[0072] 2. Electrochemical performance analysis of rosin-wood pitch-based porous carbon materials

[0073] The electrochemical performance of the rosin-wood pitch-based porous carbon material electrode was tested in a 6 mol / L KOH three-electrode system. Figure 3As shown. The preparation method of the rosin-wood pitch-based porous carbon material electrode and the construction method of the three-electrode system are as follows: 40 mg of rosin-wood pitch-based porous carbon material, 8 mg of conductive carbon black and 8 mg of polyvinylidene fluoride (PVDF) are weighed respectively, the rosin-wood pitch-based porous carbon material and the conductive carbon black are firstly placed in a mortar and fully ground and mixed, and then PVDF is added and continued to be ground until the three components are evenly dispersed, and then the mixed powder is transferred to a sample bottle, 30 drops of N-methylpyrrolidone is added as a dispersant, and ultrasonic treatment is performed for 30 minutes to prepare an electrode slurry. Then, nickel foam was used as the electrode current collector. The nickel foam was cut into small pieces of 1 cm×2 cm, marked and placed in an oven to dry at 80°C for 30 min to remove surface moisture. The nickel foam was then taken out and the prepared electrode slurry was evenly coated on the surface of the nickel foam. The mixture was dried at 80°C for 12 h to completely evaporate the solvent. Finally, the coated nickel foam was placed in a tablet press and kept at a pressure of 20 MPa for 30 s to tightly combine the electrode material with the current collector, thereby obtaining a working electrode that can be used for electrochemical testing.

[0074] Depend on Figure 3 It can be seen that the CV curves of rosin-wood pitch-based porous carbon materials prepared with different amounts of acrylic rosin addition at a high scan rate of 100 mV / s are all rectangular, and there is no deformation even when the scan rate increases, indicating that the samples have good rate performance (a). From the GCD charge and discharge curve (b), it can be seen that the GCD curves all present isosceles triangles, indicating that the capacitive behavior of rosin-wood pitch-based porous carbon materials is mainly a double layer, and there is no obvious voltage drop. Compared with the charge and discharge curves of other samples, RWPC-0.2 shows the longest charge and discharge time (752 s at 1 A / g) and the highest specific capacitance, which is consistent with the results of the CV curve. The excellent CV and GCD curves of RWPC-0.2 are mainly attributed to the material's honeycomb interconnected three-dimensional porous structure (such as Figure 4), which enables the electrolyte ions to move quickly. From the comparison of specific capacitance performance at different current densities (c), it can be seen that with the increase of current density, the specific capacitance shows a decreasing trend. The reason for this phenomenon is that the lower current density allows the electrolyte ions to diffuse fully in the electrode, thereby obtaining a longer charge and discharge time. At 1A / g, the specific capacitances of RWPC-0, RWPC-0.05, RWPC-0.1, RWPC-0.15, RWPC-0.2 and RWPC-0.25 are 279 F / g, 325 F / g, 353 F / g, 270 F / g, 376 F / g and 275 F / g, respectively. The specific capacitance of RWPC-0.2 is the largest, indicating that the addition of an appropriate amount of acrylic rosin can improve the electrochemical performance. In addition, at a current density of 0.5-10 A / g, the capacitance retention rate of RWPC-0.2 is 72%, which has good electrochemical performance.

[0075] At the same time, the electrochemical impedance spectroscopy of rosin-wood pitch-based porous carbon materials prepared with different amounts of acrylic rosin addition is shown in Figure 2. Figure 5 As shown in Figure 2, it represents the electrode resistance and the diffusion and transfer behavior of electrolyte ions. Figure 5 It can be seen that the Nyquist plots of rosin-wood pitch-based porous carbon materials prepared with different amounts of acrylic rosin addition all show similar shapes, that is, they are all composed of three parts. The line in the low-frequency region is approximately perpendicular to the x-axis, representing pure capacitance behavior; Warburg resistance is observed in the mid-frequency region, which represents the diffusion impedance of the substance in the electrochemical reaction; and the high-frequency region is a semicircle, representing the electron transfer impedance of the electrochemical reaction. The semicircle in the high-frequency region represents R 2 , which represents the internal resistance of the material. All samples were fitted with an equivalent circuit. The R 2 Minimum, 0.092 Ω.

[0076] Since the RWPC-0.2 sample exhibits higher specific capacitance and lower impedance, a 5000-cycle cycle stability test was performed on the RWPC-0.2 sample. The results are as follows: Figure 6 As shown. Figure 6 It can be seen that the capacitance retention rate of the RWPC-0.2 sample is 83.8% after charge and discharge cycles at a current density of 10 A / g, which indicates that the RWPC-0.2 sample has excellent cycle stability.

[0077] 3. Rheological properties analysis of printing ink

[0078] In this example, rosin-wood tar-based carbon material RWPC-0.2 was used as the active substance, PEDOT:PSS as the conductive agent, and glycerol-based nanocellulose as the rheological agent and thickening agent to prepare four printing inks (DIW-0, DIW-40, DIW-120, DIW-200). By observing the slurry state and the morphology of the printed objects, the flow state and printability of the printing ink samples can be preliminarily evaluated. The results are shown in Figure 7 . As shown by Figure 7 , after the beakers filled with the four inks were placed upside down for 1 h, each sample only tilted slightly (a), indicating that the obtained printing inks have a relatively stable solid structure. At the same time, it can be judged from the morphology of the printed slurry that the lines printed by the inks have a certain linear morphology and are uniform (b), and no flow deformation occurred when printing the interdigital electrodes (c). Therefore, it can be shown that the composite ink system has printability.

[0079] To further understand the rheological behavior of the ink, rheological property characterization was carried out, and the results are shown in Figure 8 . As shown by Figure 8 , as the shear rate increases, the viscosity gradually decreases (a), which indicates that the prepared composite inks all belong to non-Newtonian fluids and have the characteristics of shear thinning. The shear thinning property is crucial for the extrusion-based 3D printing technology, which can ensure the smooth flow and precise deposition of the ink during the printing process. At the same time, when the ink is subjected to a certain shear force, its dispersion system will yield, changing from an elastic body (G′>G″) to a viscous body (G′<G″), showing typical viscoelastic body characteristics (b). This is because in the initial stage (G′>G″), the ink all shows solid-state characteristics; as the oscillatory strain increases, the cross-linked network inside the ink begins to crack; finally, when the yield stress point (G′<G″) appears, it indicates that the internal network of the ink has been completely destroyed, and at this time the ink flows out of the nozzle in a liquid state.

[0080] To more intuitively understand the rheological behavior of the ink during the extrusion process, a thixotropy test was carried out, and the results are shown in Fig. 9 . As shown by Fig. 9 , the whole test process is divided into three stages: (1) Static stage: Maintain for 120 s at a relatively small shear rate (0.01 s -1 ), at this time the ink is in a static state and shows a relatively high viscosity; (2) Extrusion stage: Suddenly apply a relatively large shear rate (100 s -1 ) and continue for 10 s. During this process, the ink breaks through the yield stress point, the viscosity drops sharply, and it turns into a liquid state and is extruded; (3) Recovery stage: Resume the relatively small shear rate (0.01 s -1), and lasted for 170s, the ink quickly returned to the high viscosity state before the test, which ensured the ability to maintain the shape during the printing process.

[0081] 4. Surface morphology analysis of 3D printed interdigitated electrodes

[0082] In order to study the surface morphology of 3D printed electrodes, a variety of characterization methods were used to systematically analyze the printed electrodes. Fig.10 .Depend on Fig.10 It can be seen that the interdigitated electrodes prepared by 3D printing have excellent shape conformality and high-precision characteristics, indicating that the 3D printing process used is reliable (a). It can be further seen from the FESEM image (b) that the interdigitated electrodes prepared by printing show good conformality, and there are no defects such as connection between adjacent interdigits, which can effectively avoid the formation of short circuits between different interdigits, and its small electrode spacing is conducive to the rapid transfer and diffusion of electrons and ions, thereby improving the performance of the capacitor. In addition, further observation of the printed electrodes using biological cryo-electron microscopy shows that the printed electrodes have a rich pore structure. This porous feature can significantly increase the specific surface area of ​​the electrode, promote the adsorption and desorption of electrolyte ions, and thus improve the capacitance performance (cd) of the capacitor.

[0083] 5. Electrochemical performance of printed electrodes

[0084] 3D printing can be used to achieve specific material routing and stacking methods. The distance between electrodes can be adjusted according to actual needs to improve the diffusion and transport of electrolyte ions in the electrodes. Rosin-wood pitch-based carbon material (RWPC-0.2) has a high specific capacitance and can reach 376 F / g at a current density of 1 A / g. It is one of the candidate materials for electrochemical devices. The CV curves of electrodes prepared by 3D printing using different composite inks prepared by RWPC-0.2 are shown in Figure 2. Fig.11 As shown. Fig.11 It can be seen that for electrodes prepared with different composite inks, the CV curve area increases with the increase in the amount of rosin-wood pitch-based carbon material added, indicating that the electrode performance becomes better with the increase in the amount of active material added; and at a higher current scan rate (200 mV / s), the DIW ink electrode still exhibits a fast current response relative to the voltage change.

[0085] The constant current charge-discharge (GCD) curves of electrodes printed with different inks at various current densities are shown in Figure 2. Fig.12 As shown. Fig.12 It can be seen that the charge and discharge curves of all sample electrodes are close to an isosceles triangle shape, which not only proves their double-layer capacitance behavior, but also shows their good charge and discharge reversibility.

[0086] The mass specific capacitance is an important criterion for measuring the performance of electrode materials, but in practical applications, the area specific capacitance and volume specific capacitance are more important. Fig.13 As shown in Figure 2, the electrode prepared by adding more rosin-wood pitch-based carbon material exhibits higher surface capacitance. 2 When the surface capacitance can reach 460 mF / cm 2 (a) In the EIS graph, it can be seen that the transfer resistance of DIW-200 ink is small in the high-frequency region and the curve is close to the y-axis overlap in the low-frequency region, which shows that DIW-200 ink is conducive to the rapid transfer of electrons and has good capacitance characteristics.

[0087] In summary, the present invention chemically oxidizes wood asphalt with hydrogen peroxide to obtain oxidized polycyclic aromatic hydrocarbons, and then grafts rosin structure onto polycyclic aromatic hydrocarbons through acrylic rosin. The introduction of rosin molecules can achieve the regulation of the molecular spacing of wood asphalt to avoid excessive molecular accumulation, and then high-temperature activation treatment with KOH can promote K + The honeycomb porous carbon material prepared by etching and intercalation has a high specific surface area (3521.5 m 2 / g) and has a rich and adjustable mesoporous structure in the range of 2-5 nm. When used as an electrode material for supercapacitors, it shows excellent capacitance and rate performance, with a specific capacitance of 376 F / g at a current density of 1 A / g. After 5000 cycles at a current density of 10 A / g, the retention of the specific capacitance reached 83.8%. This method of adjusting the micromorphology and pore structure of carbon materials provides a way to prepare excellent supercapacitor carbon on a large scale using cheap wood asphalt precursors.

[0088] On this basis, the present invention uses solution-processed PEDOT:PSS and rosin-wood pitch-based carbon materials to prepare conductive composite inks that can be used for DIW printing. At room temperature, a DIW gel composite material with a three-dimensional interconnected hierarchical porous structure was prepared using a 3D printer. The printed all-gel DIW-based micro-interdigitated electrode supercapacitor not only has excellent 3D printing performance, but also has a high surface capacitance (460 mF / cm 2 ), excellent rate performance and good cycle stability and other excellent electrochemical energy storage characteristics. This micro supercapacitor is expected to be widely used in flexible electronics, smart wearables, the Internet of Things and other fields.

[0089] The above description is only a preferred embodiment of the present invention. All equivalent changes and modifications made according to the scope of the patent application of the present invention should fall within the scope of the present invention.

Claims

1. A method for preparing a wood pitch-based porous carbon material, characterized in that: The steps include: 1) Preparation of oxidized wood asphalt: After the wood asphalt is pre-treated by ball milling, hydrogen peroxide is added for ultrasonic mixing, and then heated in a water bath for reaction, and then washed, filtered, and dried to obtain oxidized wood asphalt; 2) Preparation of rosin-wood pitch-based porous carbon material: Grind and mix the oxidized wood pitch obtained in step 1) with chitosan and acrylic rosin, then pre-carbonize under nitrogen protection, grind and mix the obtained product with KOH, activate under nitrogen protection, and acid-wash, water-wash and dry the activated product to obtain a rosin-wood pitch-based porous carbon material; The mass ratio of oxidized wood asphalt, chitosan, acrylic rosin and KOH used in step 2) is 1:1:0.2:

3.

2. The method for preparing a wood pitch-based porous carbon material according to claim 1, characterized in that: In step 1), the amount of hydrogen peroxide used is 0.5-3 mL per gram of wood asphalt.

3. The method for preparing the wood pitch-based porous carbon material according to claim 1, characterized in that: In step 1), the ball milling pretreatment time is 1-9 h; the reaction temperature is 60-90° C. and the reaction time is 1-3 h.

4. The method for preparing wood pitch-based porous carbon material according to claim 1, characterized in that: In step 2), the pre-carbonization temperature is 400-600°C and the time is 0.5-3 h; the activation temperature is 600-1000°C and the time is 0.5-3 h.

5. A wood pitch-based porous carbon material prepared by any method as claimed in any one of claims 1 to 4.

6. A use of the wood pitch-based porous carbon material as claimed in claim 5 in the preparation of a 3D printed supercapacitor, characterized in that: The asphalt-based porous carbon material is used as a raw material, and is added into a PEDOT:PSS aqueous solution together with glycerol system nanocellulose and ethylene glycol, and stirred and mixed, and then heated and concentrated at 60-100° C. for 2-4 hours to prepare a asphalt-based composite ink, which is then used for 3D printing and further assembled into a supercapacitor; The usage ratio of the wood asphalt-based porous carbon material, glycerol-based nanocellulose, ethylene glycol and PEDOT:PSS aqueous solution is (0.04-0.2) g:1 g:4 mL:16 mL.

7. The use according to claim 6, characterized in that The glycerol system nanocellulose is prepared by placing 10 g of pulp into 50-100 g of glycerol, adding 0.2-1 g of a sulfuric acid solution with a volume concentration of 72% as a catalyst, heating in an oil bath at 80-120° C. and vigorously stirring for 1-4 h to completely dissolve the pulp board; after the reactants are cooled to room temperature, adjusting the pH to neutral with a NaOH solution with a mass concentration of 5%, and then transferring to a colloid mill for mechanical treatment for 0.5-1 h to obtain the nanocellulose.

8. The use according to claim 6, characterized in that: The mass concentration of the PEDOT:PSS aqueous solution is 1%, wherein the mass ratio of PEDOT to PSS is 1:2.5.

Citation Information

Patent Citations

  • Modified hard carbon material as well as preparation method, electrode and application thereof

    CN114212770A

  • Non-structural activated carbon and process for the production thereof

    GB446889A